ESG and Islamic Accounting for Sustainable Islamic Finance: A Qualitative Study - Siregar, Retnawati (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study explores the alignment between Environmental, Ssocial, and Governance (ESG) principles and Shariah-based Islamic accounting to support sustainable Islamic finance. The objective is to analyze conceptual synergies, identify operational barriers, and propose an integrative framework through a qualitative approach involving a systematic review of academic literature, regulatory documents, and financial reports. Findings reveal that Shariah principles, such as the prohibition of riba, emphasis on social benefit, and environmental protection, align with environmental, social, and governance objectives. Instruments like Green Sukuk in Indonesia and Malaysia and Shariah-compliant microfinance demonstrate practical applications for inclusive development and eco-friendly projects. However, challenges include the lack of standardized Shariah-compliant metrics, regulatory gaps, and low stakeholder awareness. The study recommends developing integrated environmental, social, and governance standards, updating regulatory frameworks, and enhancing stakeholder education to improve transparency and accountability. In conclusion, integrating environmental, social, and governance principles with Islamic accounting can strengthen the sustainability of Islamic finance and support global sustainable development goals, though it requires regulatory harmonization and capacity building.